Diagnosing 'Ignorance': conversion, race, and reform among Muslims in Madras and Ceylon - Tschacher, Torsten (Nidān, 2024)
This article analyses the impact of colonial racialisation on Muslim reform movements in the Madras Presidency and Ceylon. It argues that that the internal racialisation of Muslims into ‘racially foreign’ ‘born Muslims’ and ‘racially Indian’ converts had direct consequences on the manner in which Muslim projects of religious reform in the colonial period were formulated. In the Madras Presidency, the Malayalam-speaking Mappilas and the Tamil-speaking Labbais were identified as communities of ‘converts’ with a thin ‘mixed-race’ elite, and consequently addressed by reform movements primarily as Muslim Malayalis and Tamils, who not only needed to purge their Islam of religious practices that were conceived of as remnants of their ‘Hindu’ identities prior to conversion, but also to remove ‘secular’ Arabic elements, such as the use of the Arabic script to write Malayalam and Tamil, in order to become properly ‘modern’ members of their respective ethno-linguistic groups. In Ceylon, in contrast, the claims to Arab-descent by local Tamil-speaking Muslims were recognised by the colonial state. Consequently, the Ceylon Muslim Revival, despite emerging from a similar social position as reform-movements in Madras, and similarly aiming at the upliftment of Muslims in terms of English-style education and the introduction of ‘modernity’, was more concerned with a quasi-secular Arabisation of its constituency rather than with religious purification.